His Name is Stephen: Getting Creative with Writing - Stella Júlía Ágústsdóttir 1976- (2014)
This paper is my B.A. thesis written for the English department at the University of Iceland. The paper is a venture into the creative writing world and contains an original novella and an exposition about the process of writing a novella. The first part of the paper is the novella His Name is Stephen which is a psychological thriller consisting of over 10,100 words. The novella follows a young woman named Janice as she tries to cope with the death of her brother at a young age and the loss of her son later in life. It becomes evident that Janice is unable to cope with the difficulties surrounding these events and is institutionalized. It explores how the mental breakdown of a mother can affect a family and tear it apart. The husband, Mike, loves his wife, but feels conflicted by his desire and need to protect their son from his own mother. Likewise it explores the inner workings of a woman dealing with delusional episodes and how she can escape from reality. The second part of the paper consists of an exposition which follows the path of a writer during the writing process. This part of the paper is just shy of 4,000 words and is followed by a detailed character sketch. The exposition shows how an idea grows into characters that follow a plot creating a story.